Treosulfan or busulfan plus fludarabine as conditioning treatment before allogeneic haemopoietic stem cell transplantation for older patients with acute myeloid leukaemia or myelodysplastic syndrome (MC-FludT.14/L): a randomised, non-inferiority, phase 3 trial. Issue 1 (January 2020) - Beelen, Dietrich Wilhelm; Trenschel, Rudolf; Stelljes, Matthias; Groth, Christoph; Masszi, Tamás; Reményi, Péter; Wagner-Drouet, Eva-Maria; Hauptrock, Beate; Dreger, Peter; Luft, Thomas; Bethge, Wolfgang; Vogel, Wichard; et al.
Summary: Background: Further improvement of preparative regimens before allogeneic haemopoietic stem cell transplantation (HSCT) is an unmet medical need for the growing number of older or comorbid patients with acute myeloid leukaemia or myelodysplastic syndrome. We aimed to evaluate the efficacy and safety of conditioning with treosulfan plus fludarabine compared with reduced-intensity busulfan plus fludarabine in this population. Methods: We did an open-label, randomised, non-inferiority, phase 3 trial in 31 transplantation centres in France, Germany, Hungary, Italy, and Poland. Eligible patients were 18–70 years, had acute myeloid leukaemia in first or consecutive complete haematological remission (blast counts <5% in bone marrow) or myelodysplastic syndrome (blast counts <20% in bone marrow), Karnofsky index of 60% or higher, and were indicated for allogeneic HSCT but considered at an increased risk for standard myeloablative preparative regimens based on age (≥50 years), an HSCT-specific comorbidity index of more than 2, or both. Patients were randomly assigned (1:1) to receive either intravenous 10 g/m 2 treosulfan daily applied as a 2-h infusion for 3 days (days –4 to –2) or 0·8 mg/kg busulfan applied as a 2-h infusion at 6-h intervals on days –4 and –3. Both groups received 30 mg/m 2 intravenous fludarabine daily for 5 days (days –6 to –2). The primary outcome was event-free survival 2 years after HSCT. The non-inferiority margin was a hazard ratio (HR) of 1·3. Efficacy was assessed in all patients who received treatment and completed transplantation, and safety in all patients who received treatment. The study is registered with EudraCT (2008–002356–18) and ClinicalTrials.gov (NCT00822393 ). Findings: Between June 13, 2013, and May 3, 2016, 476 patients were enrolled (240 in the busulfan group received treatment and transplantation, and in the treosulfan group 221 received treatment and 220 transplanation). At the second preplanned interim analysis (Nov 9, 2016), the primary endpoint was met and trial was stopped. Here we present the final confirmatory analysis (data cutoff May 31, 2017). Median follow-up was 15·4 months (IQR 8·8–23·6) for patients treated with treosulfan and 17·4 months (6·3–23·4) for those treated with busulfan. 2-year event-free survival was 64·0% (95% CI 56·0–70·9) in the treosulfan group and 50·4% (42·8–57·5) in the busulfan group (HR 0·65 [95% CI 0·47–0·90]; p<0·0001 for non-inferiority, p=0·0051 for superiority). The most frequently reported grade 3 or higher adverse events were abnormal blood chemistry results (33 [15%] of 221 patients in the treosulfan group vs 35 [15%] of 240 patients in the busulfan group) and gastrointestinal disorders (24 [11%] patients vs 39 [16%] patients). Serious adverse events were reported for 18 (8%) patients in the treosulfan group and 17 (7%) patients in the busulfan group. Causes of deaths were generally transplantation-related. Interpretation: Treosulfan was non-inferior to busulfan when used in combination with fludarabine as a conditioning regimen for allogeneic HSCT for older or comorbid patients with acute myeloid leukaemia or myelodysplastic syndrome. The improved outcomes in patients treated with the treosulfan–fludarabine regimen suggest its potential to become a standard preparative regimen in this population. Funding: medac GmbH.